2016
DOI: 10.3389/fpsyg.2016.01066
|View full text |Cite
|
Sign up to set email alerts
|

Can We Talk through a Robot As if Face-to-Face? Long-Term Fieldwork Using Teleoperated Robot for Seniors with Alzheimer's Disease

Abstract: This work presents a case study on fieldwork in a group home for the elderly with dementia using a teleoperated robot called Telenoid. We compared Telenoid-mediated and face-to-face conditions with three residents with Alzheimer's disease (AD). The result indicates that two of the three residents with moderate AD showed a positive reaction to Telenoid. Both became less nervous while communicating with Telenoid from the time they were first introduced to it. Moreover, they started to use more body gestures in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…Researchers have recently explored the role of social robots in a variety of domains, including elder care [6,7], shop-keeping [1,2,4,3,55], hotels [8], education [9], travel [10], and as personal 24:2 M. Doering et al companions [11,12]. As the capability of artificial intelligence increases, this trend is likely to continue.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have recently explored the role of social robots in a variety of domains, including elder care [6,7], shop-keeping [1,2,4,3,55], hotels [8], education [9], travel [10], and as personal 24:2 M. Doering et al companions [11,12]. As the capability of artificial intelligence increases, this trend is likely to continue.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are studies on robots used for older adults in the community, such as using Telenoids for communication support for older adults [9]. Older adults with Alzheimer's disease showed positive reaction to the Telenoid [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are studies on robots used for older adults in the community, such as using Telenoids for communication support for older adults [9]. Older adults with Alzheimer's disease showed positive reaction to the Telenoid [9]. Another study in Taiwan explored 33 healthy, community-dwelling Taiwanese older adults who responded at a higher level of acceptance toward the more service-oriented robot than the more companion-oriented robot considering attitude, perceived adaptiveness, and perceived usefulness [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, two issues were realized regarding living with a human-type communication robot as a strategy; to improve cognitive functions and prevent cognitive decline in the elderly [12]. With robot therapy, it was found that only a few aspects of its capabilities, when examined closely, were effects derived from the viewpoints of nursing practices and human care [13] [14]. In this regard, robot therapy has not been generalized, and more descriptions and discussions about its practical utility are required.…”
Section: Introductionmentioning
confidence: 99%